2019
DOI: 10.1002/fsn3.1242
|View full text |Cite
|
Sign up to set email alerts
|

Acheta domesticus (Cricket) feed resources among smallholder farmers in Lake Victoria region of Kenya

Abstract: The quality of domesticated crickets depends on the choice of feed substrate that has a direct impact on the economic viability of the farming operation. This study assessed the popular local cricket feeds in the Lake Victoria region. Data were collected through individual interviews, focus group discussions, personal observations, and growth experiments. Kales, sweet potato leaves, ugali, and banana peels were the most preferred by the farmers. Crickets fed on kales and sweet potatoes had a significantly high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 23 publications
(36 reference statements)
0
14
0
Order By: Relevance
“…Magara et al (2019) also found that diet protein content caused a strong sex ratio bias in offspring, with a female-biased sex ratio observed in S. icipe populations reared on higher protein (16-41%) diets of wheat bran, soybean, and/or pumpkin leaf. Higher-protein diets were also correlated with higher-protein content in A. domesticus (Bawa et al, 2020;Oloo et al, 2020).…”
Section: Crude Proteinmentioning
confidence: 85%
See 4 more Smart Citations
“…Magara et al (2019) also found that diet protein content caused a strong sex ratio bias in offspring, with a female-biased sex ratio observed in S. icipe populations reared on higher protein (16-41%) diets of wheat bran, soybean, and/or pumpkin leaf. Higher-protein diets were also correlated with higher-protein content in A. domesticus (Bawa et al, 2020;Oloo et al, 2020).…”
Section: Crude Proteinmentioning
confidence: 85%
“…ADF, acid detergent fiber; C, carbohydrate; CF, crude fiber; CP, crude protein; DM, dry matter; NDF, neutral detergent fiber. 2016), microbial counts and relative abundance (Ng'ang'a et al, 2020), maturity period (Oloo et al, 2020), nitrogen efficiency, phosphorus content, total fatty acids (Oonincx et al, 2015), developmental rate, glycoalkaloid concentrations, fatty acid content and composition (Sorjonen et al, 2019), daily DM intake, and periodic FCR (Vaga et al, 2019).…”
Section: Insect Measurementsmentioning
confidence: 99%
See 3 more Smart Citations